Association between generalized joint hypermobility, temporomandibular joint hypertranslation and temporomandibular disorders: a scoping review - Samilla Pontes BRAGA; Carolina Ortigosa CUNHA; Ambrosina MICHELOTTI; Leonardo Rigoldi BONJARDIM; Paulo César Rodrigues CONTI (Journal of Applied Oral Science)
Abstract Generalized Joint Hypermobility (GJH) is one of the pathophysiological contributing factors for the development of temporomandibular disorders (TMD). There are, however, several counterpoints on the potential relation between TMD and joint hypermobility, especially when considering the temporomandibular joint (TMJ), event known as TMJ hypertranslation. Additionally, there is no consensus regarding the clinical and imaging diagnostic criteria for such condition. Hence, this scoping review addresses the association between GJH, TMJ hypertranslation and TMD, highlighting the lack of consensus concerning TMJ hypertranslation diagnosis. Eligibility criteria included book sections, clinical trials, meta-analyses, multicenter studies, observational studies, and reviews published in English between 1964 and 2024. Bibliographic search was conducted on the PubMed, SciELO, LILACS and Science Direct databases using the following Medical Subjective Headings (MeSH) terms: “temporomandibular joint disorders,” “temporomandibular joint,” “joint instability” and “joint dislocations.” “TMJ hypermobility” and “TMJ subluxation,” non-indexed terms, were applied as individual searches in the same databases. Manual search was performed in selected works by cross-referencing the included studies and book sections. Additional search was conducted in the grey literature. All searches were performed from January to June 2024. After selection, 54 texts were included. While some studies suggest that joint hypermobility (generalized or TMJ specific) may be a risk factor for TMD, especially of the intra-articular type, others rule out this association. No consensus on the potential association between joint hypermobility and TMD was achieved due to the diverse methodologies used to define TMJ hypertranslation diagnosis. More robust and controlled studies are needed to establish a diagnostic criteria and, consequently, understanding of its potential repercussions on masticatory structures, as well as management and prevention of the clinical manifestations.